(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
This paper analyses the various intermedial relations between video games and pictorial art. The research method used is a multiple‑case study, which enables a broad approach to this phenomenon. The results achieved reflect the video game permeability with pictorial art, through hybridization processes, the activation of art works as game elements or characters, and the creation of pictorial spaces within the video pleasent picture.